Berczeli Anzelm Károlyhoz - Göncz Árpád (Fond 380 Berczeli Anzelm Károly írói hagyatéka, 1980)
Fond 380 Berczeli Anzelm Károly írói hagyatéka > Berczeli Anzelm Károly levelezése > Berczeli Anzelm Károlyhoz írt levelek